Cachexia index as a potential biomarker for cancer cachexia and a prognostic indicator in diffuse large B‐cell lymphoma. Issue 6 (21st October 2021) - Go, Se‐Il; Park, Mi Jung; Park, Sungwoo; Kang, Myoung Hee; Kim, Hoon‐Gu; Kang, Jung Hun; Kim, Jung Hoon; Lee, Gyeong‐Won
Abstract: Background: Cancer cachexia is known to adversely affect the clinical course in patients with malignant lymphoma. The cachexia index (CXI) is a potential biomarker of cancer cachexia, and its implications for the prognosis and treatment outcome of lung cancer and aggressive lymphoma has been assessed in previous studies. Methods: A total of 267 patients diagnosed with diffuse large B‐cell lymphoma who were treated with rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R‐CHOP) immunochemotherapy were retrospectively reviewed. The CXI was calculated as the skeletal muscle index (SMI) × serum albumin/neutrophil–lymphocyte ratio (NLR). Although previous studies measured the SMI using the muscles of the L3 vertebral level, the present study used both the L3 vertebral muscles and the pectoralis muscles (PM) at the T4 vertebral level to measure the SMI. Depending on the type of muscles used, the CXI was termed the L3‐CXI or PM‐CXI. Using sex‐specific cutoff values for CXI, the patients were categorized as follows: (i) high‐CXI group (high L3‐CXI and high PM‐CXI), (ii) intermediate‐CXI group (high L3‐CXI and low PM‐CXI), and (iii) low‐CXI group (low L3‐CXI and low PM‐CXI). Results: Complete responses to R‐CHOP were obtained in 145/173 (83.8%), 25/36 (69.4%), and 27/57 (47.4%) patients in the high‐CXI, intermediate‐CXI, and low‐CXI groups, respectively ( P < 0.001). Treatment‐related anaemia (15.6%, 30.6%, and 26.3%, P = 0.038), thrombocytopenia (21.4%, 36.1%, and 43.9%, P < 0.001), febrile neutropenia (23.7%, 44.4%, and 36.8%, P = 0.022), and any nonhaematologic toxicity (31.2%, 44.4%, and 54.4%, P = 0.001) of Grade 3 or more were more common in the lower CXI groups than in the higher‐CXI groups. Early treatment discontinuation for reasons other than lymphoma progression also occurred more frequently in the low‐CXI group (24/57, 42.1%) compared with the intermediate‐CXI (5/36, 13.9%) and high‐CXI (18/173, 10.4%) groups ( P < 0.001). Median overall survival in the high‐CXI, intermediate‐CXI, and low‐CXI groups was not reached, 50.6 months, and 14.5 months, respectively ( p < 0.001). Multivariable analysis showed that low CXI was an independent negative prognostic factor for overall survival (hazard ratio 2.103, 95% confidence interval 1.278–3.460, P = 0.003). Conclusions: We suggest that in patients with diffuse large B‐cell lymphoma, the CXI is a biomarker for cancer cachexia that can predict survival, treatment response, treatment‐related toxicity, and compliance with R‐CHOP. Patients were more clearly stratified by this new CXI category compared with the classifications described in previous studies.